Rusiah textile inventory management system - Nor Zaharah Ayu, Maarof (2019)
Inventory management system is widely use in most industries. These project is specifically focusing on replace a current approaches method that had been used by small-medium company. These company specially provides varies textile products such as scarf, women clothing and accessories that matched with outfits. This Inventory Management System help the company to ensure the business run smoothly with function register, manage, product category. The most common problems in previous method is the person in charge doing mistakes while write down the details of data in the file records. This system is able to help the company to manage the inventory more effectively. For this enhancement, Rapid Application Development (RAD) methodology is applied. This enhancement proposed to make sure deliver the project in better condition.